5y-6+y+46=6y+40-2y

Simple and best practice solution for 5y-6+y+46=6y+40-2y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5y-6+y+46=6y+40-2y equation:


Simplifying
5y + -6 + y + 46 = 6y + 40 + -2y

Reorder the terms:
-6 + 46 + 5y + y = 6y + 40 + -2y

Combine like terms: -6 + 46 = 40
40 + 5y + y = 6y + 40 + -2y

Combine like terms: 5y + y = 6y
40 + 6y = 6y + 40 + -2y

Reorder the terms:
40 + 6y = 40 + 6y + -2y

Combine like terms: 6y + -2y = 4y
40 + 6y = 40 + 4y

Add '-40' to each side of the equation.
40 + -40 + 6y = 40 + -40 + 4y

Combine like terms: 40 + -40 = 0
0 + 6y = 40 + -40 + 4y
6y = 40 + -40 + 4y

Combine like terms: 40 + -40 = 0
6y = 0 + 4y
6y = 4y

Solving
6y = 4y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-4y' to each side of the equation.
6y + -4y = 4y + -4y

Combine like terms: 6y + -4y = 2y
2y = 4y + -4y

Combine like terms: 4y + -4y = 0
2y = 0

Divide each side by '2'.
y = 0

Simplifying
y = 0

See similar equations:

| -6x-7x=-52 | | 2(3+5x)-3=23 | | 6t^5+3t^4=-12t^3 | | 9x+5=9-(9x-3) | | 21x-28y+7=0 | | 49w^2-81g^2=0 | | e^9x+8=13 | | 81v^2-126v+49= | | 900x^2-1800x+900=0 | | x^2+14x+15= | | 4w^2+28wd+49d^2=0 | | t^2-3.2t-3.2=49 | | 40x^2+30x=0 | | 4r^2-36r+81=0 | | b^4-144=0 | | 5(9c^2-64)=0 | | 45c^2-32= | | -5x^3+4x^2=0 | | 3y^2+8y=12y+15 | | 7(x+1)-6x=-3 | | 5x-3=8x+12 | | 4x+2x-5=7 | | 15a^2-17ab-4b^2=0 | | 5x-4=7x+6 | | 8b^2-18bc-5c= | | 3(4)+3= | | 12s^3+20s^2-48s= | | 3(4x-7)=7x-3 | | x^2+17x+72= | | 25s^2+70s=-49 | | 8(x+1)-7x=-5 | | 12s^3+20s^2-48s=0 |

Equations solver categories